2002
DOI: 10.1016/s0925-4439(01)00106-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular quality control machinery contributes to the leukocyte NADPH oxidase deficiency in chronic granulomatous disease

Abstract: Chronic granulomatous disease (CGD) is an inherited immunodeficiency disease caused by defects in leukocyte NADPH oxidase. Various inherited defects in one of the membrane-bound components of NADPH oxidase, gp91-phox, cause X-linked (X91) CGD. Analysis of three patients with X91 CGD revealed that different mechanisms of molecular quality control lead to the common phenotype of absence of mature membrane-bound NADPH oxidase complex in leukocytes. In the first patient, aberrant intron splicing created a prematur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…However, when we used neutrophils from a CGD patient along with normal controls as the source of superoxide in our experiments (Fig. 6, fifth and sixth panels), the suppressive activity of NO was significant in both conditions even though almost no ROS was produced by the CGD neutrophils (data not shown and [20]). These results suggest that NO might suppress eosinophil binding to VCAM-1 in a mechanism different from that of superoxide-mediated enhancement of cell binding.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, when we used neutrophils from a CGD patient along with normal controls as the source of superoxide in our experiments (Fig. 6, fifth and sixth panels), the suppressive activity of NO was significant in both conditions even though almost no ROS was produced by the CGD neutrophils (data not shown and [20]). These results suggest that NO might suppress eosinophil binding to VCAM-1 in a mechanism different from that of superoxide-mediated enhancement of cell binding.…”
Section: Discussionmentioning
confidence: 86%
“…Children deficient in components of NADPH oxidase are defective in superoxide generation and hence suffer from recurrent and serious infections. This condition is termed CGD [20][21][22]. Many investigations have shown that ROS produced by leukocyte NADPH oxidase modulate the expression of adhesion molecules involved in leukocyte trafficking [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the activation of leukocytes usually leads to activation of NADPH oxidase and production of reactive oxygen species (ROS), which are crucial for effective immune defense [5][6][7]. Our previous studies showed that ROS produced by activated granulocytes affect eosinophil binding to VCAM-1 [8].…”
Section: Introductionmentioning
confidence: 99%